The Abundance of Odonata Insect in Lebak Swamp, Bukit Baru, Palembang, Indonesia - Novin Teristiandi; Riyanto Riyanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Lebak swamp in Bukit Baru has been largely degraded due to reclamation activity. Lebak swamp plays important role as land resource in Bukit Baru, Palembang. The aim of this study was to examine the composition of Odonata in lebak swamps in Bukit Baru, Palembang, Indonesia. The transect line (1 km) was used to collect odonata in the study area. This study recorded 8 species during the study period. The highest diversity of odonata was found in site A1. The highest abundance of odonata was recorded at site A2 and A4 and dominated by Ceriagrion coromandelianum and Orthetrum sabina. Neurothemis ramburii had the lowest abundÃÂ ance at site A1 and A2, but absent at site A3 and A4. The occurrence of odonate species are lower at site around anthropogenic activity suggests the need to protect the lebak swamp so that such uncommon species will not go into local extinction. Neurothemis ramburii can become potential species to evaluate the rate of disturbed environment.ÃÂ